Iconography and ideograms. A preliminary outline of an experimental study on the non-verbal languages of Ancient Mesopotamian cultures - di Fede, Claudia (Cognitive philology, 2011)
Cylinder seal represents one of the most typical elements of the Near Eastern cultures used to mark goods and to avoid any tampering. This study's number one goal was to verify the possible relations between some of the architectural elements drawn on the seals and some of the cuneiform signs. The investigation was carried out starting from the decomposition of the whole scene, isolating those represented buildings. After that it was possible, through comparison to establish in at least thirty cases, a uniformity between images and signs. To develop this subject it was needed the use of two different kinds of analysis: an iconographic one totally based on the realistic representation of each element and the other one based on the meaning of the images drawn on the seals. Both of the analysis appeared to be really satisfactory, reaching in seven of the cases the complete identity and correspondence. Althought it needs to be reminded that above mentioned hypotesis are just about the analyzed sample, so their affective scientific relevance may only be verified by testing other samples. We commit ourselves in the near future to realize new studies, extending both geographic area and considered samples, starting from the matches already confirmed.